Evaluation of a two-sample process for prevention of ABO mistransfusions in a high volume academic hospital. Issue 3 (15th July 2018) - Glisch, Chad; Jawa, Zeeshan; Brener, Alina; Carpenter, Erica; Gottschall, Jerome; Treml, Angela; Karafin, Matthew Scott
Abstract : Background: Acute haemolytic transfusion reactions due to ABO incompatible blood transfusion remain a leading cause of transfusion-associated morbidity and mortality in the USA. Erroneous patient identification and specimen labelling account for many errors that lead to ABO mistransfusions; these errors are largely preventable. Methods: Our hospital requires a two-sample process of ABO/Rh typing prior to transfusion. Both samples must be drawn independently. To prevent simultaneous sample draw, our second sample tube has a unique pink top that is only available from the blood bank and can only be sent to the patient's floor once the first sample arrives in the lab. We performed an audit of this process from 19 March to 30 July 2014 and 19 March to 30 July 2015. Results: We reviewed type and crossmatch orders for 2702 new patients during the audit period and 824 patients (30.5%) required transfusion. All patients evaluated received compatible blood, and no mistransfusions were recorded using this method. Three per cent of testing was performed incorrectly, which safely defaulted to giving type O blood. Conclusions: The two-sample protocol used by our institution can decrease the risk of mistransfusion. Our protocol was relatively inexpensive, safe, efficient and practical for adaptation by other hospitals.